Towards the Development of an IsiXhosa Adaptation of the MacArthur-Bates Communicative Development Inventory for Toddlers - Whitelaw, Emma (School of Languages and Literatures, 2019)
In this thesis, I draw on experiences of the isiXhosa segment of the pre-pilot research phase and first rural, toddler pilot for the adaptation of the MacArthur-Bates Communicative Development Inventory (CDI) into Southern African languages. 1 The adaptation stems from the growing dissatisfaction regarding the dearth of speech and language assessments and therapeutic tools currently available in South Africa for isiXhosa or other local languages (Pascoe and Smouse, 2012; Demuth, 2007). Such tools are of fundamental importance since failure to accurately diagnose communication difficulties hinders appropriate intervention. If improperly addressed, communication difficulties can hamper the essential development of literacy skills and academic success (see Shonkoff and Phillips, 2000). Reliable research on child language acquisition is thus critically needed in order to inform culturally and linguistically appropriate assessments that can lead to accurate diagnosis and treatment of communication disorders, and ultimately improve children’s early childhood development trajectories. Data from the pre-pilot and pilot study informs discussions about monolingual isiXhosa-speaking toddlers’ lexical and grammatical acquisition. I furthermore discuss the need for the adaptation of such inventories to local circumstances, and I problematise the assumption that Western linguistic constructs, ontologies, and epistemologies are appropriate for the CDI exercise as applied to Bantu languages. The findings of this study furthermore contribute to existing scholarship on how children acquire words and morphemes. Findings as such will be of use to clinicians and speech pathologists, especially in informing vital language and communication rehabilitation in early childhood development. I additionally hope that the results presented will inform cross-linguistic scholarship on child language acquisition, paving the way for future research as well as the creation of bi- and multilingual CDIs.